ANALISIS RELASI SISTEM PERPAJAKAN DAN PREKONOMIAN MASYARAKAT DI INDONESIA - Nugroho, Wahyu; Yubaidi, Ahmad (LPPM Universitas Bina Bangsa, 2025)
This research discusses the tax system in Indonesia, focusing on its foundations, principles and development. It also identifies the impact of each type of tax on the economy and society and reviews the main problems in the implementation of the tax system. As a state revenue collection mechanism, the tax stelsel has a significant impact on state revenues that are able to support various government programs, especially in infrastructure development. Optimal tax revenue allows the government to build roads, bridges, and other public facilities, which in turn boost economic growth. However, tax policy also has implications for economic inequality in society.